Iatrogenic endometriosis harbors somatic cancer-driver mutations. Issue 1 (14th November 2018) - Lac, V; Verhoef, L; Aguirre-Hernandez, R; Nazeran, T M; Tessier-Cloutier, B; Praetorius, T; Orr, N L; Noga, H; Lum, A; Khattra, J; Prentice, L M; Co, D; et al.
Abstract: STUDY QUESTION: Does incisional endometriosis (IE) harbor somatic cancer-driver mutations? SUMMARY ANSWER: We found that approximately one-quarter of IE cases harbor somatic-cancer mutations, which commonly affect components of the MAPK/RAS or PI3K-Akt-mTor signaling pathways. WHAT IS KNOWN ALREADY: Despite the classification of endometriosis as a benign gynecological disease, it shares key features with cancers such as resistance to apoptosis and stimulation of angiogenesis and is well-established as the precursor of clear cell and endometrioid ovarian carcinomas. Our group has recently shown that deep infiltrating endometriosis (DE), a form of endometriosis that rarely undergoes malignant transformation, harbors recurrent somatic mutations. STUDY DESIGN, SIZE, DURATION: In a retrospective study comparing iatrogenically induced and endogenously occurring forms of endometriosis unlikely to progress to cancer, we examined endometriosis specimens from 40 women with IE and 36 women with DE. Specimens were collected between 2004 and 2017 from five hospital sites in either Canada, Germany or the Netherlands. IE and DE cohorts were age-matched and all women presented with histologically typical endometriosis without known history of malignancy. PARTICIPANTS/MATERIALS, SETTING, METHODS: Archival tissue specimens containing endometriotic lesions were macrodissected and/or laser-capture microdissected to enrich endometriotic stroma and epithelium and a hypersensitive cancer hotspot sequencing panel was used to assess for presence of somatic mutations. Mutations were subsequently validated using droplet digital PCR. PTEN and ARID1A immunohistochemistry (IHC) were performed as surrogates for somatic events resulting in functional loss of respective proteins. MAIN RESULTS AND THE ROLE OF CHANCE: Overall, we detected somatic cancer-driver events in 11 of 40 (27.5%) IE cases and 13 of 36 (36.1%) DE cases, including hotspot mutations in KRAS, ERBB2, PIK3CA and CTNNB1 . Heterogeneous PTEN loss occurred at similar rates in IE and DE (7/40 vs 5/36, respectively), whereas ARID1A loss only occurred in a single case of DE. While rates of detectable somatic cancer-driver events between IE and DE are not statistically significant ( P > 0.05), KRAS activating mutations were more prevalent in DE. LIMITATIONS, REASONS FOR CAUTION: Detection of somatic cancer-driver events were limited to hotspots analyzed in our panel-based sequencing assay and loss of protein expression by IHC from archival tissue. Whole genome or exome sequencing, or epigenetic analysis may uncover additional somatic alterations. Moreover, because of the descriptive nature of this study, the functional roles of identified mutations within the context of endometriosis remain unclear and causality cannot be established. WIDER IMPLICATIONS OF THE FINDINGS: The alterations we report may be important in driving the growth and survival of endometriosis in ectopic regions of the body. Given the frequency of mutation in surgically displaced endometrium (IE), examination of similar somatic events in eutopic endometrium, as well as clinically annotated cases of other forms of endometriosis, in particular endometriomas that are most commonly linked to malignancy, is warranted. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by a Canadian Cancer Society Impact Grant [701603, PI Huntsman], Canadian Institutes of Health Research Transitional Open Operating Grant [MOP-142273, PI Yong], the Canadian Institutes of Health Research Foundation Grant [FDN-154290, PI Huntsman], the Canadian Institutes of Health Research Project Grant [PJT-156084, PIs Yong and Anglesio], and the Janet D. Cottrelle Foundation through the BC Cancer Foundation [PI Huntsman]. D.G. Huntsman is a co-founder and shareholder of Contextual Genomics Inc., a for profit company that provides clinical reporting to assist in cancer patient treatment. R. Aguirre-Hernandez, J. Khattra and L.M. Prentice have a patent MOLECULAR QUALITY ASSURANCE METHODS FOR USE IN SEQUENCING pending and are current (or former) employees of Contextual Genomics Inc. The remaining authors have no competing interests to declare. TRIAL REGISTRATION NUMBER: Not applicable.